Penerapan Literasi Teknologi Informasi dan Komunikasi (ICT) dalam Pembelajaran di SDN 88 Palembang - Nasywa Salsabila Putri; Hidayatullah; Arini Ayu Audia; Vitara; M.Hilman Hibatullah (Advances In Education Journal, 2025)
This study aims to describe the implementation of Information and Communication Technology (ICT) literacy at SDN 88 Palembang through interviews and questionnaires involving the principal, teachers, and students. The research employed a descriptive qualitative approach using interview guides and questionnaires as instruments. The results show that the school has supporting ICT policies and facilities such as computers, projectors, and Wi-Fi, although they remain limited. Teachers show positive attitudes and actively use digital media, while students demonstrate enthusiasm toward ICT-based learning. The main challenges lie in limited facilities and unstable internet connections. Overall, ICT literacy at SDN 88 Palembang is considered good but requires improvements in infrastructure, continuous teacher training, and parental support.